168 Endometrial and colon cancer risk assessment in women with lynch syndrome: provider comfort, knowledge, and current practice. (13th November 2020) - Bramblet, R; Weaver, A; Langstraat, C; Maurer, S; Swanson, C; Sherman, M; Kisiel, J; Wick, M; Bakkum-Gamez, J
Abstract : Objective: Women with Lynch Syndrome (LS) experience a lifetime risk of endometrial (EC) and colon (CC) cancer of up to 57%, and the risk is approximately equal for each LS gene. Our objective was to determine knowledge of EC and CC risks, screening guidelines, and management recommendations among healthcare providers caring for women with LS. Methods: An anonymous survey was sent to providers in primary care, ob/gyn, gynecologic oncology, gastroenterology, and clinical genomics across a healthcare enterprise. Data reported using descriptive statistics. Results: 215 of 1198(18%) providers responded and 89% either had or anticipated caring for women with LS. Of 167 providers who completed the survey, 51% were primary care and 38% reported feeling at least somewhat uncomfortable with cancer screening for LS. Among the 77 (46%) currently caring for women with LS, 39% counsel that the risk of CC is approximately equivalent to the risk of EC; 34% counsel that the risk of EC is lower than the risk of CC or consistent with the general population. Additional counseling rates shown in table 1 . Conclusions: A large portion of providers who care for LS patients feel uncomfortable with making cancer screening recommendations. One-third of providers potentially underestimate a woman's risk of EC, and most do not recognize that EC could be the presenting cancer for women. Improved education of providers regarding cancer screening and risk reduction options for women with LS may improve adherence to management guidelines.